Nexus between Profitability and Environmental Performance of Indian Firms – An Analysis with Granger Causality - Vinayagamoorthi, Vasanth; Murugesan, Selvam; Kasilingam, Lingaraja; Ramachandran, Rajesh Ramkumar (International Journal of Energy Economics and Policy, 2015)
Sustainable Development enhances the human life, with good eco facilities. The way to move toward the sustainable development is by giving best solutions to the issues of unbalanced ecological, environmental and economic development. This paper investigates the relationship between the environmental performance and the profitability variables such as ROA, ROE, ROCE, and ROS of the sample firms in India. Granger Causality Test was used to examine bidirectional causality running from Energy Intensity to Profitability of the Firm. The study identified causal relationship that existed among the environmental performance and profitability of the firm. Further, it is found that there was an inverse relationship between ROCE and energy intensity of the firm while direct relationship existed among ROA, ROE, ROS and Energy Intensity. It is suggested that the practitioners, policy makers etc. may adopt the environment friendly technologies and encourage the Indian firms to use more energy efficient technology. Keywords: Environmental Performance; Firms’ Profitability; Energy Intensity; Causal Effect JEL Classifications: L25; M14; Q51; Q01; Q4